An exploration of pornography use with offenders: attitudes and effects - Mellor, Emily J. (2020)
Background: The concept of allowing offenders, residing in a secure environment, access to pornography can be a contentious issue. Pornography on its own comes with a large taboo surrounding it, but adding into the equation the idea of allowing people who may have committed devastating crimes access to pornography, can trigger anger and apprehension. The research regarding pornography use with sexual offenders is contradictory at times which increases the difficulty when attempting to understand its effects. Pornography is used by a large number of individuals currently residing in secure services; however, there is very little research exploring this. Thus, it can be difficult at times, as professionals working with offenders, to make decisions regarding their access to pornography. As such this thesis targets these gaps within the literature.